Notochordal cell conditioned medium (NCCM) regenerates end-stage human osteoarthritic articular chondrocytes and promotes a healthy phenotype. Issue 1 (December 2016) - Müller, Sebastian; Acevedo, Lina; Wang, Xiaomei; Karim, M.; Matta, Ajay; Mehrkens, Arne; Schaeren, Stefan; Feliciano, Sandra; Jakob, Marcel; Martin, Ivan; Barbero, Andrea; Erwin, W.
Abstract Background Notochordal cell conditioned medium (NCCM) derived from non-chondrodystrophic dogs has pro-anabolic and anti-catabolic effects upon nucleus pulposus (NP) cells. Here, for the first time, we assessed the ability of NCCM to influence the production of extracellular matrix and inflammatory proteins by healthy and osteoarthritic human chondrocytes within engineered cartilage tissues. We hypothesized that, similar to its action on NP cells, NCCM exerts metabolic and anti-catabolic effects on human articular chondrocytes and has the potential to significantly counteract inflammatory mediators. Methods Chondrocytes from nine non-osteoarthritic patients and from six osteoarthritic (OA) donors at the time of total knee arthroplasty were chondro-differentiated in pellets for 2 weeks. Non-OA pellets were exposed for 72 hours to IL-1β/TNF-α and then cultured up to 14 days in 2 % FBS-supplemented NCCM or 2 % FBS-supplemented medium (control (ctr)). OA pellets were cultured in NCCM or ctr medium without pro-inflammatory treatment. Tissues after each culture phase were analyzed biochemically (GAG/DNA), (immuno-) histologically (collagen I, II and GAG) and by Western blotting. Supernatants were analyzed by ELISA. Results Response to NCCM was age and disease dependent with healthy chondrocyte pellets (from donors >55 years of age) recovering their glycosaminoglycan (GAG) contents to baseline levels only with NCCM. OA pellets treated with NCCM significantly increased GAG content (1.8-fold) and levels of hyaluronic acid link protein (HAPLN), fibromodulin and SOX-9. The catabolic proteins (matrix metalloproteinase (MMP)-3 and MMP-13) and pro-inflammatory enzyme levels (cyclooxygenase-2 (COX-2)) were markedly reduced and there was significantly reduced secretion of pro-inflammatory chemokines (IL-6 and IL-8). Conclusions NCCM restores cartilage matrix production of end-stage human OA chondrocytes towards a healthy phenotype and suppresses the production of inflammatory mediators. Harnessing the necessary and sufficient factors within NCCM that confers chondroprotection and regenerative effects could lead to a minimally invasive agent for treatment of degenerative and inflammatory joint diseases.